A case study - Implementing a registered nurse professional recognition program across a Queensland hospital and health service. (January 2020) - Bamford-Wade, Anita; Lavender, Samantha; Massey, Debbie; Anderson, Vinah; Clayton, Samantha; Johnston, Amy
Abstract: Ongoing advancement and documentation of professional development is required to maintain nursing registration and competency to practise in Australia and many other countries. All Australian registered nurses are required to undertake a minimum of 20 h of continuing professional development annually and demonstrate competence to practice; this is a criterion for nursing registration. Many health care organisations nationally and internationally develop programs to support such processes, assisting nurses to formally document their ongoing education and commitment to best practice, and clearly demonstrate their ongoing continuing professional development. Such programs align with the MAGNET ® principles of providing structural empowerment, exemplary professional practice and new knowledge, innovations and improvements. This study describes the implementation, evaluation and impact of the registered nurse professional recognition program undertaken by one Hospital and Health Service in South East Queensland using Donabedian's structure, process outcome framework. The registered nurse professional recognition program was implemented to invest in and develop the nursing workforce by providing an opportunity for registered nurses to assess and document their professional skills, knowledge and expertise that are critical to the provision of safe and cost-effective patient and family-centred care. Highlights: Continuing professional development is a key aim of recognition programs. The recognition program is aligned with the Australian national standards. This recognition program documents nurse education and clinical expertise. The recognition program aligns with the MAGNET ® model.